Pengembangan Bahasa Melalui Media Roda Putar Pada Kelompok B PAUD Terpadu AL-Madinah Kota Parepare - Halifah, Syarifah; Palintan, Tien Asmara; Sari, Putri Indah (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This research was conducted to develop children's language skills in class B1 PAUD AL-Madinah Integrated PAUD, Parepare City, which still needs to be developed. There are many problems with children's language skills, namely some children are unable to communicate and express their opinions or communicate their wishes to others. There are many problems with children's language skills, namely some children are unable to communicate and express their opinions or communicate their wishes to others. One way to involve children in active learning is to provide unique and creative learning media. The assessment carried out by the researcher in this activity was that the child understood the rules of the game, enjoyed and appreciated reading, and the child repeated more complex sentences. Spinning wheel playing activities have succeeded in developing language in group B children in the AL-Madinah Integrated PAUD because the use of rotary wheel media can affect all aspects of children, making children more active and interactive, learning more optimal and more fun. When used, these media can generate attention, interest and motivation to learn, make students active and interactive, increase understanding and learning can be fun and optimal.